Effects of Sacubitril/Valsartan on left ventricular pressure-volume relationship in heart failure. (3rd October 2022) - Stegmann, T; Parentin, L; Schirmer, S H; Hagendorff, A; Laufs, U; Lavall, D
Abstract: Background: In patients with heart failure (HF) and reduced ejection fraction, Sacubitril/Valsartan (S/V) reduces the risk for death and hospitalisations. However, the underlying mechanism for these beneficial effects of S/V, is still lacking. Methods: Consecutive patients with symptomatic HF and LV ejection fraction (EF) ≤40% who were assigned to S/V were prospectively included in this study (n=117). Non-invasive pressure volume loops were obtained from echocardiography with simultaneous arm-cuff blood pressure measurement. By this method, LV end-systolic elastance (Ees), effective arterial elastance (Ea) and ventricular-arterial coupling (Ea/Ees) were calculated. LV end-diastolic pressure was derived from the E/e' ratio. This is a prespecified interim analysis of 50 patients with completed 6 months of follow-up. The study is registered with ClinicalTrials.gov, NCT04498780. Results: Mean age was 61.8±18.6 years and 12 (24%) patients were females. Ischaemic heart failure was present in 22 (44%), non-ischaemic aetiology in 24 (48%), and myocarditis in 4 (8%) patients. 34 (68%) patients were on the target dose of S/V after 6 months of treatment. At 6 months, LV end-diastolic volume (110±28 ml/m 2 vs. 87±31 ml/m 2, p<0.0001) and end-systolic volume (78±26 ml/m 2 vs. 52±26 ml/m 2, p<0.0001) were reduced, hence mean LVEF increased (30±7% vs. 42±11%, p<0.0001). LV end-diastolic pressure was significantly reduced (21±3.9 mmHg vs. 18±2.7 mmHg, p<0.0001). These hemodynamic changes were associated with improved NYHA functional class (8% class III vs. 20% at baseline), reduced median NT-proBNP level (2398 pg/ml, interquartile range [IQR]: 1185–6034 to 813 pg/ml, IQR: 299–1971, p<0.001) and increased mean six-minute walk test (6MWT) distance (356.8m (±150.5) at baseline to 415.0m (±397.0) at six months, p=0.003). LV end-systolic elastance (Ees), arterial elastance (Ea) and the ventricular-arterial coupling ratio Ea/Ees remained similar at 6 months of follow-up compared to baseline (p=ns). Conclusion: After 6 months of treatment with Sacubitril/Valsartan, LV remodelling and reduced LV filling pressures were observed. These changes were associated with improvements in functional capacity, natriuretic peptide levels and NYHA functional class. Thus, the study provides important mechanistic insides into the hemodynamics of angiotensin–neprilysin inhibition in heart failure which might help to individualize therapy. Funding Acknowledgement: Type of funding sources: None.